Caffeic acid phenethyl ester (CAPE) protects against acute urogenital injury following pneumoperitoneum in the rat. (February 2014) - Rifaioglu, Murat Mehmet; Davarci, Mursel; Nacar, Ahmet; Alp, Harun; Celik, Murat; Sefil, Nebihat Kaplan; Inci, Mehmet
Abstract Purpose: Our aim is to determine the biochemical and histologic changes induced in the kidneys, testis and prostate on possible ischemia and reperfusion (I/R) injury caused by pneumoperitoneum (PNP) in a rat model and to evaluate the ability of protective effects of caffeic acid phenethyl ester (CAPE). Methods: Twenty-eight adult male Wistar albino rats were randomly divided to one of three treatment groups, with seven animals in each group. Sham, laparoscopy (L), and laparoscopy plus CAPE (L + C) group were subjected to 60 min of PNP with 15 mmHg one hour before the desufflation period. Total oxidant status (TOS) and total antioxidant status (TAS) levels were determined in kidney, testis, and prostate. Kidney and testis tissues were removed to obtain a histologic score. Also, Johnsen scoring system was used for testicular tissue analysis. Results: L group had significantly higher TOS and lower TAS levels on kidney and testis compared to the other groups. In prostate biochemical analysis, there was not any difference between groups. No difference was found between groups according to kidney and testis tissues' histologic evaluation. In evaluation of Johnsen scoring, L group showed significant lower score compared to the other two groups. Conclusions: Increased intraabdominal pressure (IAP) had an oxidative effect on kidney and testis but not on prostate in rats. Moreover, it could affect the testicular Johnsen score. All these adverse effects of IAP on both kidney and testis could be prevented by CAPE administration.